2007
DOI: 10.1016/j.cej.2006.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Observer design for the Selective Catalytic Reduction of NOx in a loop reactor

Abstract: The aim of this work is to show how to design a soft-sensor to monitor the Selective Catalytic Reduction (SCR) of NOx with NH3 in a loop reactor, i.e. a loop-shape system made of N units with periodical variation of the feed position. The design procedure of Zeitz (1977) is used and, even if the design procedure remains basically heuristic, some general guidelines to design the observer are given. The proposed observer is demonstrated to allow for a quick and reliable estimation of the inlet NOx concentration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The dots represent the results by experiments, while the lines stand for the results by model prediction with Eq. (13). It can be seen that the model predictions and experimental results agree well.…”
Section: Mimic Of Catalytic Decomposition Over Circulating Ashes Withsupporting
confidence: 69%
See 1 more Smart Citation
“…The dots represent the results by experiments, while the lines stand for the results by model prediction with Eq. (13). It can be seen that the model predictions and experimental results agree well.…”
Section: Mimic Of Catalytic Decomposition Over Circulating Ashes Withsupporting
confidence: 69%
“…Circulating ashes, the circulating bed materials in the CFB boilers, are generally with narrower size distribution, larger specific area and less carbon content than those bed materials only residing in the furnace and could be excellent catalyst to accelerate N 2 O decomposition [9][10][11]. Interacting with NH 3 , the circulating ash can even accelerate the destruction of NO and N 2 O at the same time, and thus it was suggested that NH 3 could be added at the cyclone entrance to reduce NO and N 2 O emission from CFB boilers [11][12][13]. Though the importance and effectiveness of the catalytic effect of circulating ash were recognized, the associated chemical kinetics has not been carefully studied.…”
Section: Introductionmentioning
confidence: 99%
“…This model allows to derive stability conditions for the control scheme and suggest a control scheme for a realistic system with one sensor, at fixed position in lab coordinates, in each unit. Thus, the control should automatically adjusts V sw to assure its value within the range (13).…”
Section: Controlmentioning
confidence: 99%
“…Other advanced approaches, such as the use of observers or soft sensors [10,13] for forced unsteady-state reactors, have been proposed to control a single traveling temperature wave.…”
Section: Controlmentioning
confidence: 99%
“…For this purpose, an algorithm, whose detailed description was not reported, was employed by the authors for the reconstruction of the temperature pattern. Other advanced approaches, such as the use of observers or soft sensors for forced unsteady-state reactors, have been proposed to control a single traveling temperature wave. …”
Section: Introductionmentioning
confidence: 99%